Two new neoavian taxa with contrasting palaeobiogeographical implications from the early Miocene St Bathans Fauna, New Zealand - Trevor H. Worthy; R. Paul Scofield; Steven W. Salisbury; Suzanne J. Hand; Vanesa L. De Pietri; Michael Archer (Journal of Ornithology, 2022)
Two new neoavian landbirds are reported from the early Miocene St Bathans Fauna from New Zealand. Aegotheles zealandivetus sp. nov. is described from several bones, among which, notably, the tarsometatarsus shows more similarity to New Guinean taxa than to Australian—New Zealand species. Zealandornis relictus gen. et sp. nov. is described from a distal end of a humerus and placed in the new family Zealandornithidae, tentatively among the ‘higher landbirds’ Telluraves, with most similarity to coliiforms. The humerus is of similar size to that of species of Colius and its gracile shaft and very shallow sulcus scapulotricipitalis suggests reduced flying ability. The new species of Aegotheles reinforces the Australasian nature of the Zealandian fauna, while in contrast, Zealandornis relictus gen. et sp. nov. appears to have no close relatives. It is as distinct as Acanthisittidae and Strigopidae among birds, or Leiopelmatidae and Sphenodontidae among the herpetofauna, and like them, represents a similar relictual taxon. Together they confer a highly evolutionarily distinctive nature to the Zealandian fauna concomitant with a minimal 60 million years of isolation.